Konsumsi dan Konversi Pakan Ternak Puyuh Petelur (Coturnix-coturnix J.) dengan Penambahan Tepung Kulit Kayu Manis (Cinnamomum burmannii) pada Pakan: Consumption and Conversion of Laying Quail (Coturnix-Coturnix J.) with Additions Cinnamon Bark Flour (Cinnamomum Burmannii) on Feed - Fitriani Fitriani; Intan Dwi Novieta; Nevyani Asikin; Yusriani Yunus (Anoa: Journal of Animal Husbandry, 2023)
There are several studies which state that Cinnamomum burmannii flour can be used as a natural feed additive for livestock at a certain level. This research was conducted to determine the effect of adding cinnamon bark powder (Cinnamomum burmannii) to laying quail (Coturnix-coturnix japonica) feed on consumption and conversion. This study used 120 laying quails. The method used in this study was a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The four treatments included K0: control or without administration of cinnamon bark flour, K1: addition of 2.5% cinnamon bark flour, K2: addition of 5% cinnamon bark flour, and K3: addition of 7.5% cinnamon bark flour to feed. The research was conducted during the grower period until the peak of production. The data obtained were analyzed using analysis of variance (ANOVA) followed by the average difference test using Duncan. The results of the analysis of variance showed that the effect of adding cinnamon bark powder to the feed had no significant effect (P>0.05) on feed consumption and conversion. The highest ration consumption was the K1 treatment with a cinnamon bark powder concentration of 2.5% with an average of 17.79 g/head and the lowest was the K3 treatment with a cinnamon bark powder concentration of 7.5% with an average of 17.73 gr /tail. Whereas in the conversion value the average value in the K0 treatment is relatively the same as the K1 and K2 treatments, while the K3 gets the highest average value.